Cluster based pre-scaling up of improved malt barley technologies at Kofele district of West Arsi zone, Oromia regional state, Ethiopia - Sintayehu Abebe; Martha Gichamo (Open Journal of Plant Science - Peertechz Publications, 2021)
Pre-scaling up of malt barley was conducted at Kofele District of West Arsi zone of Oromia regional state, to increase farmers' capacity in production and management practices. Kofele district was selected due to its potential for barley production. One "kebele" was selected in collaboration with Kofele district agricultural and natural resource expert purposively based on potential for malt barley production and availability of land for cluster farming purpose. From selected "Kebele" 85 farmers were selected as team leader, with 410 of follower farmers and a total of 495 farmers were selected for the activity in cropping season (2018/19). An improved variety of malt barley called IBON 174/03 distributed to farmers. Ninety (90) quintals of malt barley were given for the selected farmers. 80 quintals of them were basic seed class whereas the rest 10 quintals had a pre-basic seed class. The seed covered the land size of 72 ha by the malt barley during the production year (2018/19).Training were arranged and delivered on production of malt barley, and chemical applications methods. Besides this awareness on production and packages of malt barley was also delivered to the farmers on the set of June 2019 which was sponsored by Ethiopian Institute of Agricultural Research (EIAR)-AGP2 program. Continues Monitoring and evaluation have been done at different time with different experts. Exchange visit as well as both villages based and large scale field days were arranged for further promotion of malt barley to other potential areas. Malt barley is potential crop in the highlands of west Arsi Zone in general and at Kofele District in particular. The crop is used for household consumption as well as industrial crop in generating income for small holder farmers. IBON 174/03 was acceptable during field day by farmers due to their disease tolerant and early maturity. After harvesting farmers like the variety IBON 174/03 due to its productivity (high yield per hectare). From one hectare the productivity of improved malt barley IBON 174/03 an average grain yields 40.2q/ha was recorded. Thus, highland farmers should use IBON 174/03 variety of malt barley in order to increase their malt barley production and generate more income for their livelihood. Further dissemination of malt barley is more expected from concerned body and addressing potential areas.